A new barracudina (Aulopiformes, Paralepididae, Stemonosudis) from Somalia, with additional records of S. siliquiventer from the Caribbean Sea - Hsuan-Ching Ho; Tsung-Yu Yang (ZooKeys)
A new species, Stemonosudis adenensis sp. nov., of slender barracudina is described based on a specimen collected off Somalia, Western Indian Ocean. The new species differs from its congeners by having a uniformly brown body, without distinct black patches; nostrils slightly before the posterior end of the maxilla; anus above the tip of the appressed pelvic fin; lateral-line scales: prepelvic 39, predorsal 48, preanal 59, total 81; vertebrae: prepelvic 38, prehaemal 42, predorsal 46, preanal 59, caudal 53, and total 95; and total gill rakers 68. Additional records of Stemonosudis siliquiventer Post, 1970 from the Caribbean Sea are also provided.